2002
DOI: 10.1063/1.1452665
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of transition curvature by magnetic force microscopy

Abstract: A technique, based on magnetic force microscopy ͑MFM͒, has been developed to quantify the curvature of recording written transitions. By evaluating the phase deviation and coherence of MFM imaged recording tracks, the on-track transition curvature can be precisely measured to nanometer level or less while minimizing relevant imaging noise associated with MFM tips or recording media. The magnetization curvature properties are characterized quantitatively using the proposed technique at different recording condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…In all calculations, the influence of peak curvatures was compensated via a technique developed by Liu et al [17]. The magnetic cluster size is derived in such a way: a noise image was extracted from the written bits; then the noise matrix was averaged in cross-track direction to obtain a line profile; finally, the auto-correlation length of the resulting line profile was calculated and was defined as the magnetic cluster size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all calculations, the influence of peak curvatures was compensated via a technique developed by Liu et al [17]. The magnetic cluster size is derived in such a way: a noise image was extracted from the written bits; then the noise matrix was averaged in cross-track direction to obtain a line profile; finally, the auto-correlation length of the resulting line profile was calculated and was defined as the magnetic cluster size.…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic force microscopy (MFM) is a useful tool for measuring magnetic behaviors of microscopic areas in magnetic recording media [14]. There are generally two kinds of MFM measurement techniques: (i) ex situ measurement in the absence of external magnetic field, which is generally used for the observation of magnetization distribution and the associated analysis [15][16][17]; and (ii) in situ measurement in the presence of an external field either normal or parallel to film plane [18]. The latter is helpful for investigation in detail of the switching behavior in microscopic scale, for instance, observation of DC-erasure process in magnetic recording media [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been commonly used to evaluate the density of magnetic materials such as magnetic recording media [4,5]. Our group has applied a magnetic force microscope technique to evaluate various kinds of structural and functional materials, and we found that this technique was useful in understanding the degradation mechanism of these materials [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%